Rural development in Nigeria : proceedings of the 1972 annual conference of the Nigerian Economic Society - Nigerian Economic Society (Ibadan : Nigerian Economic Society, 1972)
This is a proceedings of the 1972 annual conference of the Nigerian Economic Society. Areas covered include: Nigerian social objectives an rural sector; agricultural productivity; Fiscal policy ad rural development; rural credit; Industrialisation among others.
lje 09/04/2018
Loans
Keywords: Rural development; Agricultural productivity; Fiscal policy; Rural credit; Rural sector; Nigeria